Modernization of the Company’s Fixed Assets: Critical Factors that Affect the Capital Budgeting Decisions - Shchurina, Svetlana V.; Prunenko, Marina A. (Journal of Reviews on Global Economics, 2018)
Modernization of the company’s fixed assets is a necessary condition for its development and competitiveness. Assessing projects and efficient allocation of the capital depend on the project requirements. The identification of the critical factors makes it possible to compile a realistic investment budget of the company. It also contributes to the optimal solution of the problem of modernization of fixed assets. The capital investment decision of project ranking plays a crucial role in capital investment decisions. The business concerns prioritize the various projects on the base of the kind of project a firm has at a particular point of time. Project ranking is dependent on the fact as to how much would a particular project return as well as which project has the ability to provide the business, a maximum value. The development of recommendations to improve the company’s policies of modernization of fixed assets under the investment budget project makes the right accents for the targeted usage of funds.